WORK-LIFE BALANCE, WORKLOAD, AND SUPERVISORY SUPPORT AS DETERMINANTS OF FEMALE EMPLOYEE JOB SATISFACTION: EVIDENCE FROM THE MANUFACTURING SECTOR IN CENTRAL JAVA - Fatwa Zuhanea (ITB AAS Indonesia Surakarta, 2020)
This study examines the influence of work-life balance, workload, and supervisory support on job satisfaction among female employees in the manufacturing sector in Central Java, Indonesia. The growing participation of women in manufacturing industries raises critical concerns about their well-being and job satisfaction, which directly affects organizational productivity. Drawing on the Conservation of Resources (COR) Theory, this research proposes that work-life balance and supervisory support positively affect job satisfaction, while workload negatively affects it. A quantitative approach was employed using purposive sampling of 138 female employees from five garment and textile companies in Banyumas and Cilacap Regencies. Data were collected using a structured questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The results indicate that work-life balance (β = 0.312, p < 0.001) and supervisory support (β = 0.289, p < 0.01) significantly and positively affect job satisfaction, while workload (β = −0.241, p < 0.05) has a significant negative effect. The model explains 54.7% of the variance in job satisfaction (R² = 0.547). These findings provide managerial implications for HR practitioners in manufacturing firms to develop flexible work policies and supervisory training programs tailored to the needs of female employees. Keywords: work-life balance; supervisory support; job satisfaction; female employees; manufacturing sector